Character Education Insertion through Acculturation “Kampung Madinah”: A Living Qur’an Study of Temboro Community, Magetan East Java - Huda, M. Dimyati; Hakamah, Zaenatul (Didaktika Religia, 2023)
This article examines the social behavior and religious practices of the people of Temboro, Magetan, East Java. The religious behavior of the Temboro community is the result of the insertion of character education values based on the interpretation of Quranic texts (living qur’an) formed through acculturation. Temboro Village is dubbed as “Kampung Madinah” which has a culture similar to Madinah City in terms of dress, religious rituals and social ethics. With a qualitative method using an anthropological approach, this article is a living Qur’an research that defines character education values into the socio-religious and cultural practices of the Temboro community using reception theory, this research produces findings; first, the insertion of character education that shapes the socio-religious behavior of the Temboro community is adapted from the informal rules of kiai in Pesantren Al-Fatah Temboro. Character education in pesantren is socially constructed hidden in the community through acculturation to the recitation tradition, social ethics and daily habits. Second, the behavior and social religious attitudes of the Temboro community follow the interpretation of the Qur’anic text received from divine and human values. These values are controlled by religious authority and local wisdom.